Legal consequences of the rights of the accused, derived from its constitutional operability - Andrade Castillo, Xavier F. (Iuris Dictio, 2013)
The administration of criminal justice has had many and fundamental changes in its evolution, both from the substantive and adjective point of view. With different nuances, highlights currently a virtual consensus on the application of the criminal law of the act, and the key notion of exceptional deprivation of liberty in the process. The right to defense, with its various elements, is the cornerstone of the criminal process, is one of the most decisive victories of the legal world, is an absolute necessity in the complex specialties of criminal justice administration.